Якість, стандартизація та взаємозамінність машинобудівної продукції - Мартинов, М. А. (ХНУРЕ, 2019)
This work is aimed at improving the standardization system for transitional fits of smooth cylindrical joints, as well as at improving metrological support of measurements and control of linear parameters of smooth cylindrical joints. The object of study - the accuracy characteristics of the mates of parts - smooth cylindrical joints with transitional fit. To achieve this goal, a probabilistic-statistical method for calculating the parameters of transitional landings is proposed, which ensures interchangeability and quality of parts. A technique is proposed for selecting universal measuring instruments for monitoring the parameters of smooth cylindrical joints.